Composición química de la fauna de acompañamiento del camarón de Veracruz(Golfo de México) - Castro-González, María Isabel (1998)
Chemical composition and energy content of the shrimp by-catch used for human and livestock consumption were studied in Alvarado, Veracruz (Gulf of Mexico). Five on-board samplings were done between September 1994 and March 1995 on shrimp ships off Veracruz. The samples were frozen on board for laboratory analysis of lhe edible portion, they included 16 families and 22 species of fishes and 1 moIlusc (squid). After moisture, lhe crude protein was lhe most abundant chemical fraction (14.3 and 19.6%); carbohydrates were numerically variable in all groups (2.1 to 7.4%); ether extract (lipids) was less abundant but variable (0.5 to 3.8%), ashes were 0.10 to 0.24%. Crude energy was less variable numerically (4.5 to 5.2 kcallg); 1 2 species are used as animal feed and only Pristipomoides aquilonaris was reported as exclusively used foc this purpose: chemical composition was similar in species used for human and for Iivestock consumption; Anchoa hepsetus. Synodus foetens. Cynoscion arenarius. Upeneus parvus and Trichiurus lepturus are recornended for human consumption, specially for low economic level areas of Gulf of Mexico.